STRATEGI PROMOSI SEKOLAH MELALUI MEDIA SOSIAL DI SD HJ ISRIATI BAITURRAHMAN 2 SEMARANG - Ma`ruf, M. Anang; Bakhri, Syaiful (Institut Nahdlatul Ulama Tasikmalaya, 2024)
This research provides an overview of school promotion through social media at SD Hj Isriati Baiturrahman 2 Semarang. The aim is to find out about: 1.) School promotion strategies through social media at SD Hj Isriati Baiturrahman 2 Semarang. 2.) Supporting factors and inhibiting factors for school promotion through social media at SD Hj Isriati Baiturrahman 2 Semarang. The strategy carried out is using the 4p product, price, place, promotion strategy of course by applying the theory of management functions, namely planning, implementation and evaluation. The supporting factor related to social media-based marketing management at SD Hj Isriati Baiturrahman 2 is the school's awareness of the importance of social media as a medium of information, the active role of the school principal, sufficient infrastructure and budget for the inhibiting factors, namely the lack of involvement of the school community, negative responses, and changing algorithms.